2011
DOI: 10.1097/anc.0b013e318229be3d
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Current Strategies for Weaning Premature Infants From Supplemental Oxygen in the Outpatient Setting

Abstract: : Pediatric pulmonologists reported a wide range of practice patterns in weaning premature infants from supplemental home oxygen. Very few respondents reported using a standardized protocol. There is no consensus about whether to wean diuretics or oxygen first. The majority of providers use nocturnal oxygen saturations as an indication for readiness to wean. Growth is an important factor for oxygen weaning considered by most pulmonologists surveyed. Consensus guidelines and subsequent evaluation of such guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 36 publications
0
33
0
1
Order By: Relevance
“…Recorded pulse oximetry is widely utilized to determine when to safely discontinue supplemental oxygen in former premature infants 8–10. However, proper interpretation of recorded oximetry studies requires comparison with reference values from appropriate control patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recorded pulse oximetry is widely utilized to determine when to safely discontinue supplemental oxygen in former premature infants 8–10. However, proper interpretation of recorded oximetry studies requires comparison with reference values from appropriate control patients.…”
Section: Discussionmentioning
confidence: 99%
“…They provide reviewable accurate information about baseline oxygenation levels and the frequency of intermittent falls in oxygenation 14–17. Furthermore, recent studies suggest that overnight assessment of oxygenation is a common component of outpatient oxygen weaning protocols 8. In order for clinicians to glean meaning from oximetry data in patient populations, it is essential to obtain reference values in appropriate controls against which they can make comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 20 pediatric pulmonary programs in the US found little consensus regarding weaning strategies from supplemental oxygen, but most used prolonged home assessments of oxygenation by nocturnal pulse oximetry. 106 It is important to note that in addition to oxygen saturation, achieving adequate somatic growth and prevention or resolution of the signs of PH are important outcomes to consider prior to discontinuing supplemental oxygen therapy. When growth is poor, the use of nocturnal oxygenmay need to be extended.…”
Section: Transitional and Postdischarge Care Of Infants With Sbpdmentioning
confidence: 99%
“…Several strategies on home oxygen therapy and weaning protocols have been proposed; [22][23][24][25] however, there still remains a wide variability in practice in the pediatric providers. 26 Even the efficacy of reducing health-care expenditures in this patient population with outpatient pulmonary follow-up is unclear. However, recent literature has shown that pulmonary follow-up keeps the ER visits and hospitalization rates between mild and severe BPD patients stable 27 when normally more severe BPD patients have increased sequelae.…”
Section: Discussionmentioning
confidence: 99%